THE PROBLEM OF TERMINOLOGY AND VOCABULARY IN MODERN LINGUISTICS (Ideal Journal of Multidisciplinary Research, 2026)
This thesis describes the problems of terminology and vocabulary in modern linguistics. The problems of terminology and vocabulary in modern linguistics are a multifaceted phenomenon requiring a systematic approach to the standardization and unification of linguistic units. The diversity of lexical and terminological systems used in various linguistic schools and fields leads to ambiguity in the interpretation of linguistic phenomena, which complicates interdisciplinary interaction and communication between researchers.
Keywords: Problems, terminology, vocabulary, linguistics, global themes, specific characteristics.